Myoblast morphology and organization on biochemically micro-patterned hydrogel coatings under cyclic mechanical strain - Ahmed, Wylie; Wolfram, Tobias; Goldyn, Alexandra M.; Bruellhoff, Kristina; Rioja, Borja Aragüés; Möller, Martin; Spatz, Joachim P.; Saif, Taher A.; Groll, Jürgen; Kemkemer, Ralf (Biomaterials, 2010)
Mechanical forces and geometric constraints play critical roles in determining cell functionality and tissue development. Novel experimental methods are essential to explore the underlying biological mechanisms of cell response. We present a versatile method to culture cells on adhesive micro-patterned substrates while applying long-term cyclic tensile strain (CTS). A polydimethysiloxane (PDMS) mold is coated with a cell repulsive NCO-sP(EO-stat-PO) hydrogel which in turn is covalently patterned by fibronectin using micro-contact printing. This results in two-dimensional, highly selective cell-adhesive micro-patterns. The substrates allow application of CTS to adherent cells for more than 4 days under cell culture conditions without unspecific adhesion. The applicability of our system is demonstrated by studying the adaptive response of C2C12 skeletal myoblasts seeded on fibronectin lines with different orientations relative to the strain direction. After application of CTS (amplitude of 7%, frequency of 0.5Hz) we find that actin fiber organization is dominantly controlled by CTS. Nuclei shape is predominantly affected by the constraint of the adhesive lines, resulting in significant elongation. Morphologically, myotube formation was incomplete after 4 days of culture, but actin striations were observed exclusively on the 45° line patterns subjected to CTS, the direction of maximum shear strain.
Online verfügbar 26 September 2009
Gesehen am 16.11.2022